Analysis of the Success in Instilling Religious and Moral Values in Early Childhood - Oktari, Rici; Juliastuti, Juliastuti; Budiana, Irma; Nurrita, Teni; Abnisa, Almaydza Pratama (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
The shift in religious and moral values in early childhood is influenced by the development of technology, social media, and parenting patterns, which impact children's behaviour and character. This study examines the inculcation of religious and moral values in early childhood through school activities. The research uses a qualitative case study approach with data collection techniques including interviews, observations, and surveys. Data were processed through condensation, data presentation, and conclusion drawing. Data validity was ensured through source triangulation. The findings show an average score of 4.05, indicating the success of religious and moral value inculcation. Sitting while eating (5.00) was very good, while saying prayers before meals (3.40) and before entering the bathroom (3.00) still need reinforcement. Honesty (4.93), politeness (4.20), and social concern (3.65) were also significant. Children demonstrated good respect for parents (4.20), though misbehaviour was still low (3.40). Independence in hygiene (4.30), knowledge of religious holidays (4.45), and interfaith tolerance (4.40) were well achieved. Conclusion: The inculcation of religious and moral values in early childhood through school activities has proven successful. Children can apply values such as honesty, politeness, cleanliness, and tolerance in daily life, though some aspects still need improvement.